2020
DOI: 10.1101/2020.08.17.253542
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adrenomedullin-CALCRL Axis Controls Relapse-Initiating Drug Tolerant Acute Myeloid Leukemia Cells

Abstract: Drug tolerant leukemic cell subpopulations may explain frequent relapses in acute myeloid leukemia (AML), suggesting that these Relapse-Initiating Cells (RICs) persistent after chemotherapy represent bona fide targets to prevent drug resistance and relapse. We uncovered that the G-protein coupled receptor CALCRL is expressed in leukemic stem cells (LSCs) and RICs, and that the overexpression of CALCRL and/or of its ligand adrenomedullin (ADM) and not CGRP correlates to adverse outcome in AML. CALCRL knockdown … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In hematological malignancies, it has been extensively demonstrated that, interfering with CSC biology, sensitizes tumors to chemotherapy. A recent paper identified calcitonin receptor-like receptor (CALCRL) is highly expressed in leukemia DTPs and its depletion reduces leukemia stem cell frequency after chemotherapy [ 16 ]. Consistent with this notion, cancers with high expression of stemness gene signatures are associated with poor prognosis [ 17 , 18 ]…”
Section: What Are the Characteristics Of Drug-tolerant Cells?mentioning
confidence: 99%
“…In hematological malignancies, it has been extensively demonstrated that, interfering with CSC biology, sensitizes tumors to chemotherapy. A recent paper identified calcitonin receptor-like receptor (CALCRL) is highly expressed in leukemia DTPs and its depletion reduces leukemia stem cell frequency after chemotherapy [ 16 ]. Consistent with this notion, cancers with high expression of stemness gene signatures are associated with poor prognosis [ 17 , 18 ]…”
Section: What Are the Characteristics Of Drug-tolerant Cells?mentioning
confidence: 99%
“…Angenendt et al found that knockdown of CALCRL significantly inhibited colony formation in human myeloid leukemia cell lines, suggesting that CALCRL may be a potential therapeutic target in AML (13). In addition, Larrue et al found that CALCRL depletion reduced the frequency of leukemic stem cells in relapse-initiating cells after in vivo chemotherapy (29). CALCRL plays a role in tumor progression by mediating CGRP and ADM.…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, none of the genes belonging to the ADM receptor complex (CALCRL, RAMP2, RAMP3) showed a correlation with endogenous ADM expression. However, it has been recently reported that CALCRL, the receptor of ADM and CGRP, is also overexpressed in LSC and its genomic ablation impaired the clonogenic capacity of AML cell lines ( 50 ) and the frequency of chemotherapy-resistant cells able to initiate leukemia relapse in preclinical models ( 81 ). In contrast to ADM , CALCRL was highly expressed in NPM1 -mutated cases also carrying the FLT3 -ITD ( 50 ).…”
Section: Discussionmentioning
confidence: 99%